2002
DOI: 10.1029/2001jb000505
|View full text |Cite
|
Sign up to set email alerts
|

Microearthquakes on the Endeavour segment of the Juan de Fuca Ridge

Abstract: [1] We report the results of a 55-day microearthquake experiment on the Endeavour segment of Juan de Fuca Ridge. The network covered a 5-km section of the ridge axis centered on the Main vent field and extended 15-km off axis on the west flank. The ridge axis and flanks were seismically active, and 1750 earthquakes were located with a minimum of five travel time picks including at least one S wave. Over half the earthquakes occurred in swarms, and a waveform cross-correlation technique was used to obtain relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(120 citation statements)
references
References 65 publications
9
111
0
Order By: Relevance
“…Kellogg, 2011). This correlation suggests that the earthquakes are intimately linked to the processes of hydrothermal heat extraction, similar to findings at the EPR (Fornari et al, 2012, in (McClain et al, 1993) or that the axial earthquakes were a manifestation of thermal stresses induced by hydrothermal cooling (Wilcock et al, 2002). (Hooft et al, 2010).…”
Section: -2000 Diking Eventsupporting
confidence: 67%
See 1 more Smart Citation
“…Kellogg, 2011). This correlation suggests that the earthquakes are intimately linked to the processes of hydrothermal heat extraction, similar to findings at the EPR (Fornari et al, 2012, in (McClain et al, 1993) or that the axial earthquakes were a manifestation of thermal stresses induced by hydrothermal cooling (Wilcock et al, 2002). (Hooft et al, 2010).…”
Section: -2000 Diking Eventsupporting
confidence: 67%
“…This fault is also the western terminus of the current axial magma chamber and is the main structural control for fluid flow that feeds the southern hydrothermal fields (Delaney et al, 1992;Kelley et al, 2001b;Glickson et al, 2007). It has also been the locus of past seismic swarms (Wilcock et al, 2002). Surprisingly, both magmas and fluids appear to rise along fractures within this fault system (Gill and Michael, 2008).…”
Section: Fluidsmentioning
confidence: 99%
“…At the Mid-Atlantic ridge, b-values have been observed to vary, but they are consistently above 1 and can reach values of up to 1.5 (Kong et al, 1992;Barclay et al, 2001;Tilmann et al, 2004). Wilcock et al (2002) performed a microearthquake study on the Endeavour segment of the Juan de Fuca ridge and recorded a b-value of 1.06. These b-values suggest that seismic energy at ocean ridges is primarily released through swarms of relatively low-magnitude earthquakes.…”
Section: Discussionmentioning
confidence: 99%
“…The local tensional stresses applied to the ridge generate sporadic pulses of extension focused along or near the ridge axis [e.g., Buck et al, 2005]. Also, extension and normal faulting may have been generated locally by thermal stresses from hydrothermal cooling [Sohn et al, 1999;Wilcock et al, 2002;Sohn et al, 2004] or by magma intrusion [e.g., Rubin, 1992]. The latter mechanism has been invoked by Wilcock et al [2009] to explain the observed microseismicity patterns and focal mechanism distribution along the Endeavor segment of the Juan de Fuca Ridge.…”
Section: Mechanisms Driving Eruptions Along the Eprmentioning
confidence: 99%